PERANCANGAN MEDIA BELAJAR ANTROPOMETRI BERBASIS AUGMENTED REALITY - Ferida Yuamita; Ulfa Amalia (Jurnal Disprotek, 2023)
The media used by educators in the teaching and learning process is an important factor that influences the level of understanding of students. Innovations in learning media in the current era of technological development, can provide opportunities for educators to always strive to provide learning media that are easily accessible, understood in depth, and can function effectively. The use of appropriate learning strategies becomes a method that can be used by educators in the process of strengthening cognitive, affective, and also motoric aspects. An initial study conducted by researchers on 50 Industrial Engineering students at the Yogyakarta Technological University, showed that 32% of students had difficulty understanding the material in the Ergonomics course related to Anthropometry (measurement of human dimensions) due to the limitations of the media in the learning process of the material. This study aims to produce a design of learning media that can provide convenience for students in understanding Anthropometry material. This research and development method uses the Lee & Owens model by carrying out 4 stages, namely Assessment/analysis, Design, Development and implementation, and Evaluation stage. The result of this research is an Augmented Reality-based application called AR Anthropometry. This application provides 3-dimensional visualization using augmented reality technology equipped with materials and quizzes as a benchmark for achieving student convenience in understanding anthropometric material.